2020
DOI: 10.3390/ijms21165642
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effects of Polyphenol Intake: Current Status and Future Possibilities

Abstract: The prevalence of obesity has steadily increased worldwide over the past three decades. The conventional approaches to prevent or treat this syndrome and its associated complications include a balanced diet, an increase energy expenditure, and lifestyle modification. Multiple pharmacological and non-pharmacological interventions have been developed with the aim of improving obesity complications. Recently, the use of functional foods and their bioactive components is considered a new approach in the prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
128
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 149 publications
0
128
0
1
Order By: Relevance
“…Moreover, recent results have shown that the effects of polyphenols-enriched diet could improve weight loss and metabolic state. In any case, not all the results described in the literature agree regarding the efficacy or the molecular target of the nutritional intervention based on the use of polyphenols [24]. This discrepancy is probably due to different chemical forms of polyphenols (8000 different compounds are known) but above all the innumerable study designs (i.e., in vitro, in animal models, with or without exercise) the dosage of polyphenols, and the duration of the treatment.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, recent results have shown that the effects of polyphenols-enriched diet could improve weight loss and metabolic state. In any case, not all the results described in the literature agree regarding the efficacy or the molecular target of the nutritional intervention based on the use of polyphenols [24]. This discrepancy is probably due to different chemical forms of polyphenols (8000 different compounds are known) but above all the innumerable study designs (i.e., in vitro, in animal models, with or without exercise) the dosage of polyphenols, and the duration of the treatment.…”
Section: Introductionmentioning
confidence: 94%
“…Natural polyphenols from fruits and vegetables exert beneficial effects on human health due to their antioxidant and anti-inflammatory properties [ 1 , 2 , 3 , 4 ]; they also behave as anticancer agents on various tumor cells [ 5 ]. Polyphenols are a group of naturally occurring phytochemicals characterized by the presence of multiple hydroxyl groups on aromatic rings, and are divided into two main categories—flavonoids and nonflavonoids—based on the number of phenol rings and the way in which these rings are linked.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have been shown both in vitro and in vivo to have potential use as an antiobesity agent [ 15 – 24 ]. Also, polyphenol intake has benefic role in obese individuals [ 25 ]. In the present study, we used a high-fat diet-induced obesity mice model to verify the inhibitory effects of berberine.…”
Section: Discussionmentioning
confidence: 99%